Aplikasi Pengolahan Nilai Siswa Berbasis Web Dengan Metode Fuzzy Logic Tsukamoto (Studi Kasus : MI Bustanul Ulum Brudu) - Andrik Santoso, Muhammad; Dwi Nuryana, I Kadek; Mufarrihah, Iftitaahul (Inovate, 2020)
In the graduation criteria, the final scores of a student who determines whether or not to pass is obtained from the national exam scores and school scores in both practical and written examinations. On the other student scores can also be used as a reference in determining high achieving students and students who deserve help. Therefore, a school needs an application processing system for students can calculate and assess automatically Web based. This system uses Fuzzy Logic Tsukamoto method to determine high-achieving students and eligible students to get help from the school. This system uses four user logins that is Admin, Homeroom, Teacher, and Student. Each user login has a different system. Admin users can process student and teacher data. User Homeroom can control a students of class according to their homeroom and homeroom can print student score in the form of report. User Teachers can provide student scores according to subjects and can print reports in the form of Legers (list of student scores). User Students can see the scores obtained. Scores needed in the system that is score assignment, UH (Quiz), PTS (Mid Semester Assessment), and PAS (Final Semester Assessment). Keyword : Processing Student Scores, Fuzzy Logic Tsukamoto, Web